An Investigation into the Linguistic and Cultural Difficulties Faced By Bahraini Students Studying Arabic in International Schools in the Kingdom of Bahrain - Al Anzarouti, Ahmed Fuad; Popoola Kareem Hamed, (Technium Social Sciences Journal, 2020)
The aim of this study are in three folded: first to shed light at language, identity and culture, explore the dilemma of bilingualism, particularly in the GCC the state including the Kingdom of Bahrain, and its dangers with reference to the domination of English as a global language; second to investigate the problem of globalization and its effect on Arabic language; and third to recommend prospects for future of Arabic learners and maintaining it as the language of the Quran for Arabic and Islamic nations. The researcher used mixed method design to collect and analyse the research data.The total number of student participants was 215, with 137 boys and 78 girls. Among these students, 81 (44 boys and 37 girls were age 15 and were in Grade 10. The other (93 boys and 41 girls) were high school students age 16. Data collected from the questionnaire are analyzed quantitatively to see the frequencies and percentages of each response in the multiple-choice sections. Means were calculated for the responses and the results are presented in tables. Qualitative data, which were obtained from the open-ended questions of the students' questionnaires, teachers and students and the administrators’ interviews are discussed and triangulated with the quantitative data to respond to the questions raised in this study. The findings revealed the potential danger that Arabic confronts in the Kingdom of Bahrain in the face of global English. Students feel the need to master English because they view it as the language of knowledge in addition to the prestige it brings the user. Furthermore, the finding indicated that the educational system has failed to create an effective bilingual program that enables students to achieve proficiency in Arabic and English languages. However, the goal must be bilingualism and the schools and universities must be equipped to teach and nurture bilingualism and not assume that students learning in English will be able to maintain their Arabic.